Tingkat Fekunditas Nematoda (Meloidogyne spp.) pada Beberapa Tanaman yang Tergolong Familia Solanaceae - WULANDARI, DWI RIZKYA; SUDANA, I MADE; SINGARSA, I DEWA PUTU (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2019)
Fecundity of Nematode (Meloidogyne spp.) in Some Plants Belonging to the Solanaceae Family The Solanaceae family is a plants that has a function to meet human food. Although the production of the Solanaceae Family in Indonesia is quite high, it has not been able to fulfill the Indonesian Population needs. This is caused by several factors and one of them is the attack of pests and diseases that can cause crop failure. Pest that causes a decrease in the Solanaceae family is root bran nematodes, (Meloidogyne spp.) The purpose of the study is to determine the level of penetration and fecundity of nematodes in several plants belonging to the Solanaceae family, and to obtain species host plants that are less favored than the plants tested Thar can be used as an alternative control of nematoda. This study using a Completely Randomized Design (CRD), with 4 types of treatment each using 6 replications with 2 research objects to obtain 48 units/plant pots. The results is penetration rate and fecundity rate were highest in tomato plants, then in eggplant plants, chili plants, and the lowest in cayenne. The result can be used as an alternative to reduce the population of nematoda (Meloidogyne spp.) in the field.